Quality Schemes in the View of Telemea Cheese Consumers in Romania: Driver of Change for Competitive Marketing Strategies - Corina A. MARES; Diana E. DUMITRAS (Bulletin of University of Agricultural Sciences and Veterinary Medicine Cluj-Napoca: Horticulture, 2024)
Consumer and producer protection, rural development, preservation of rural culture, uniqueness, and product traceability are some of the characteristics that define quality schemes. Apart from the quality schemes of the European Union, there are national schemes, voluntary certifications at both national and international levels, offering consumers additional information on the quality characteristics of products. The study aimed to understand the level of knowledge of quality schemes, the buying intentions, and the willingness to pay for Telemea Cheese with quality certification label in Romania. Data collected via a questionnaire was analyzed using descriptive statistics and regression analysis. A moderate level of knowledge regarding the quality schemes was found among consumers of Telemea Cheese, with a higher percentage in the case of national quality labels. The presence of the quality certification label on the package of Telemea Cheese was more important as age increased (OR=1.135, p<0.01), for female respondents (OR=0.7038, p<0.01), and for people living in a household with children (OR=1.2787, p<0.05). Initiatives to highlight the advantages of food products with quality schemes are required to raise consumer awareness. The findings provide valuable information to develop marketing strategies to increase the value of locally produced agricultural and food products.